CHEMICAL COMPOSITION, MINERAL AND NUTRITIONAL VALUE OF DATURA METEL SEED - INDRA RAI; R. K. BACHHETI; ARCHANA JOSHI (International Journal of Pharma and Bio Sciences, 2013)
In the past few decades there has been an exponential growth in the field of herbal medicine to be a better option for their healthcare needs, owing to their natural origin and reduced side effects. Datura spp. is one of the 50 fundamental herbs used in traditional medicine. The dry flower, particularly the violet coloured, if rolled and used like cigar, will help to relive the asthma or wheezing like symptoms. The physico-chemical properties, mineral contents, fatty acid profile of oil were analysed. The % yield of the seed was 14.72%, the crude protein content of seed was 20.73%. Datura metel seeds contains rich phosphorous (690.2mg/100gm) and calcium (174.0 mg/100gm).Datura oil contains high % of linoleic acid (55.11%).This work conclude that Datura metel seeds have being potential sources of fixed oil which might be used for medicinal and other industrial applications.